Photocatalytic degradation of a cationic dye using Ag2O@CuO nanoellipsoidal photocatalyst under ultraviolet irradiation - Mohsen, Danyah M.; Al-Jubouri, Sama M.; Al-Batty, Sirhan (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The photocatalysis oxidation process is a promising technology within the series of advanced oxidation processes, which implements light-induced catalysts to generate strong oxidative species to eliminate organic pollutants from wastewater treatment. The Ag2O@CuO photocatalyst was successfully prepared by the co-precipitation method. The developed photocatalyst was characterized using X-ray diffraction, Fourier transform infrared spectroscopy, X-ray fluorescence spectrometer, field-emission scanning electron microscopy, Ultraviolet-Visible diffuse reflectance spectra, and photoluminescence spectra. The Ag2O@CuO efficiency was examined in the photocatalysis degradation of Rhodamine B (RhB) as a cationic dye under the illumination of ultraviolet light. The effect of various parameters, such as the type of light, photocatalyst dose, initial RhB concentration, and pH of the RhB solution, was studied. The results revealed that 90% degradation was achieved within 90 min at a pH of 6.8, 50 mg of a photocatalyst dose, and 10 mg/L of RhB dye under UV irradiation. However, 98% degradation of RhB dye was achieved at a pH of 10 under the same other conditions mentioned above. The kinetic study was performed based on the experimental data of the oxidative photocatalytic degradation of the RhB dye. The zero-order, pseudo-first order, and modified Freundlich kinetic models were applied to accomplish this study. The results showed that the photocatalytic oxidation of RhB dye by the Ag2O@CuO heterojunction photocatalyst followed a pseudo-first order kinetic model, with an apparent rate constant of 0.0429 min-1. Furthermore, the Langmuir-Hinshelwood model was used to investigate the RhB photocatalytic degradation kinetics of RhB at concentrations of 5-10 mg/L. The determined value of the intrinsic photocatalytic reaction rate constant was 0.7184 mg/L.min for the Ag2O@CuO heterojunction photocatalyst. Also, the equilibrium adsorption constant was 0.0767 L/mg for the Ag2O@CuO heterojunction photocatalyst.